An SNX10 mutation causes malignant osteopetrosis of infancy. Issue 4 (12th April 2012) - Aker, Memet; Rouvinski, Alex; Hashavia, Saar; Ta-Shma, Asaf; Shaag, Avraham; Zenvirt, Shamir; Israel, Shoshana; Weintraub, Michael; Taraboulos, Albert; Bar-Shavit, Zvi; Elpeleg, Orly
Abstract : Background: Osteopetrosis is a life-threatening, rare disorder typically resulting from osteoclast dysfunction and infrequently from failure to commitment to osteoclast lineage. Patients commonly present in infancy with macrocephaly, feeding difficulties, evolving blindness and deafness, and bone marrow failure. In ∼70% of the patients there is a molecularly defined failure to maintain an acid pH at the osteoclast-bone interface (the ruffled border) which is necessary for the bone resorptive activity. Methods and results: In eight patients with infantile osteopetrosis which could be cured by bone marrow transplantation, the study identified by homozygosity mapping in distantly related consanguineous pedigrees a missense mutation in a highly conserved residue in the SNX10 gene. The mutation segregated with the disease in the families and was carried by one of 211 anonymous individuals of the same ethnicity. In the patients' osteoclasts, the mutant SNX10 protein was abnormally abundant and its distribution altered. The patients' osteoclasts were fewer and smaller than control cells, their resorptive capacity was markedly deranged, and the endosomal pathway was perturbed as evidenced by the distribution of internalised dextran. Conclusions: SNX10 was recently shown to interact with vacuolar type H + -ATPase (V-ATPase) which pumps protons at the osteoclast-bone interface. Mutations in TCIRG1, the gene encoding a subunit of the V-ATPase complex, account for the majority of cases of osteopetrosis. It is speculated that SNX10 is responsible for the vesicular sorting of V-ATPase from Golgi or for its targeting to the ruffled border. A mutation in SNX10 may therefore result in 'secondary V-ATPase deficiency' with a failure to acidify the resorption lacuna. Determination of the sequence of the SNX10 gene is warranted in molecularly undefined patients with recessive 'pure' osteopetrosis of infancy.